The Genetic Variation of Apolipoprotein A-I Increases The Risk of Dyslipidemia In The Javanese Population - Danarsih, Dwi Eni; Hastuti, Pramudji; Sadewa, Ahmad Hamim (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Dyslipidemia, a risk factor for cardiovascular disease, is a public health concern in Indonesia due to its prevalence. Genetic variants in ApoA-I rs670 and rs5070 have been linked to cholesterol, insulin, and obesity levels. Research on genetic variation continues to yield diverse results in numerous populations, including the Javanese. Objective: The purpose of this study is to find out if there is a correlation between Apolipoprotein A-I rs670 and rs5070 genetic variations and dyslipidemia.Methods: This study included 60 patients with dyslipidemia and 60 Javanese ethnic controls. Cases and controls were matched according to gender and age. Patients with dyslipidemia are identified using the normal value limit for NCEP ATP III cholesterol. The genotype of the respondents was determined using the PCR-RFLP method.Results: The CT/TT genotype rs5070 was more susceptible to dyslipidemia than the CC genotype (OR 4.466; 95% CI 1.451-13.751; p 0.009). The T allele increased the probability of developing dyslipidemia compared to the C allele (OR 4.186; 95% CI 1.452-12.068; p=0.008).Conclusion: The genetic polymorphism rs5070 is linked to the prevalence of dyslipidemia. The AACC haplotype is a genetic protection against dyslipidemia.